Zsidó-keresztény jogfilozófiai elemek a szufizmusban - Falus, Orsolya (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Islam was the latest of the Abrahamic religions to develop its mystical branch, Sufism, and therefore did not precede that of the other two religions. Elements of mysticism had appeared much earlier in Judaism and Christianity. The Jewish Kabbalah flourished among Eastern Jewry under Muslim rule. The anti-heretical, orthodox teachings of Sufism, as exemplified in the works of al-Ghazali and al-Arabi, show noticeable parallels with the writings of the Jew Abraham Maimonides. Although the pursuit of complete union with God, as well as the teachings of self-surrender and asceticism, appeared in earlier centuries of Christianity, it was during the heyday of Sufism, in the 13th and 14th centuries, in the works of Meister Eckhart, that these related teachings appeared most strikingly. The aim of this study is to compare the mystical trends of the three Abrahamic religions and their natural law aspects using the method of source analysis, focusing primarily on the period when all three flourished, side by side, and in interaction with each other.